Effectiveness of innovation activity of large Russian companies - Елена Евгеньевна Первакова; Василий Александрович Чайка (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2014)
Authors: Vasiliy Alexandrovich Chaika vasily_chayka@mail.ruElena Evgenevna Pervakova National Research University The Higher School of Economics pervelen@mail.ruThe paper describes the results of studies of the dependence of the largest Russian companies on their spending on research and development. A model of the influence of spending on research and development of the market value, productivity and output.